Genealogi Perkembangan Studi Hadis dI Indonesia - Hasep Saputra (Institut Agama Islam Negeri (IAIN) Curup, 2017)
Study of hadīth from Sanad al-Ḥadīth, Ulūm al-Ḥadīth, until methodology of ḥadīth studies indicated that there was development in study hadīth with a scientific approach, deductive logic, and correlation of socio-historical context-psychological in Indonesia. Ijtihad scholars ḥadīth in Indonesia cannot be separated from sociocultural, political factor, background readings, education, madhhab and trends of thought that he holds. This study supports the notion that there is the development of ḥadīth studies in Indonesia. The above statement has similarities with other academic communities, such as Daniel Djuned (2002), R. Michael Feener (2002 ), and Muhammad Dede Rodliyana (2003). On the other hand, the statement contradictory of some other academic groups, such as Ramli Abdul Wahid (2006), Khairul Rafiqi (2012), and Martin van Bruinessen (1995) explained that the tradition of hadith studies was rare in Indonesia.